Effects of the organic UV-filter, 3-(4-methylbenzylidene) camphor, on benthic invertebrates and ecosystem function in artificial streams - Campos, Diana; Machado, Ana L; Cardoso, Diogo N; Silva, Ana Rita R; Silva, Patrícia V; Rodrigues, Andreia C M; Simão, Fátima C P; Loureiro, Susana; Grabicová, Kateřina; Nováková, Petra; Soares, Amadeu M V M; Pestana, João L T (Environmental pollution (1987), 2020)
In the last decades, the use of organic ultraviolet-filters (UV-filters) has increased worldwide, and these compounds are now considered emerging contaminants of many freshwater ecosystems. The present study aimed to assess the effects of 3-(4-methylbenzylidene) camphor (4-MBC) on a freshwater invertebrate community and on associated ecological functions. For that, artificial streams were used, and a natural invertebrate benthic community was exposed to sediments contaminated with two concentrations of 4-MBC. Effects were evaluated regarding macroinvertebrate abundance and community structure, as well as leaf decomposition and primary production. Results showed that the macroinvertebrate community parameters and leaf decomposition rates were not affected by 4-MBC exposure. On the other hand, primary production was strongly reduced. This study highlights the importance of higher tier ecotoxicity experiments for the assessment of the effects of low concentrations of organic UV-filters on freshwater invertebrate community structure and ecosystem functioning.
Keywords: Water Pollutants, Chemical; Rivers; Ecosystem; sladká voda; bezobratlí; řeky; Animals; Invertebrates; Fresh Water; zvířata; Camphor; chemické látky znečišťující vodu; ekosystém; kafr